Análisis de las intervenciones farmacéuticas a través del área de dosis unitaria en pacientes con diabetes mellitus tipo 2. - Guevara Sánchez, Vanessa Del Cisne; Armijos Solorzano, Melissa Susana (My University, 2024)
Diabetes Mellitus type 2 (DM2) is a significant chronic public health condition. The management of type 2 Diabetes Mellitus (DM2) requires a multidisciplinary health team, highlighting the crucial role of pharmacists in medication dispensing and patient education. Therefore, the objective of the work was to analyze the pharmaceutical interventions, which are performed in the area of Unit Dose of medicines in patients with Diabetes Mellitus type 2 (DM2), in the General Hospital of Machala IESS, during the period June to October 2023, for the contribution in the safety and effectiveness of pharmacological treatments. A descriptive, documentary and retrospective cross-sectional study was conducted, analyzing data from medical records of patients with Diabetes Mellitus type 2 (DM2), treated between June to October 2023 at the General Hospital of Machala. A mixed qualitative and quantitative approach was used, with a sample of 85 patients over 18 years of age. Data such as age, gender, weight and types of pharmaceutical interventions performed were recorded. Eighty-five pharmaceutical interventions were developed, including dosage adjustments and medication regimen revisions. The most common interventions were overdosing (30.6%) and underdosing (18.8%). The importance of the pharmacist in preventing errors and improving the quality of pharmacotherapy was emphasized. Most of the patients treated were women (61.2%). In addition, it was known that metformin was the drug most frequently involved in the pharmaceutical interventions (45.9%). Thus, the importance of the pharmacist's role in the Unit Dose Drug Distribution System and its contribution to the prevention of medication errors and the optimization of pharmacotherapy in these patients was demonstrated. In addition, the implications of these findings for clinical practice are discussed and recommendations for future pharmaceutical management strategies in this population are proposed. Likewise, these results are examined in order to evaluate the contribution of these interventions to the safety and effectiveness of pharmacological treatments. It is recommended to reinforce the follow-up of pharmaceutical interventions, to continue investigating their long-term impact, to implement treatment adherence education programs, and to personalize interventions according to the individual characteristics of each patient based on the factors associated with this disease.
Diabetes Mellitus tipo 2 (DM2), es una afección crónica significativa para la salud pública. El manejo de la Diabetes Mellitus tipo 2 (DM2) requiere un equipo de salud multidisciplinario, destacando el papel crucial de los farmacéuticos en la dispensación de medicamentos y la educación al paciente. Por ello, el objetivo del trabajo fue analizar las intervenciones farmacéuticas, que se realizan en el área de Dosis Unitaria de medicamentos en pacientes con Diabetes Mellitus tipo 2 (DM2), en el Hospital General de Machala IESS, durante el período junio a octubre 2023, para la contribución en la seguridad y efectividad de los tratamientos farmacológicos. Donde se dio un estudio descriptivo, documental y retrospectivo de corte transversal, analizando datos de historias clínicas de pacientes con Diabetes Mellitus tipo 2 (DM2), atendidos entre junio a octubre de 2023 en el Hospital General de Machala. Se utilizó un enfoque mixto cualitativo y cuantitativo, con una muestra de 85 pacientes mayores de 18 años. Se registraron datos como edad, género, peso y tipos de intervenciones farmacéuticas realizadas. Se desarrollaron 85 intervenciones farmacéuticas, incluyendo ajustes de dosificación y revisiones de regímenes de medicación. Las intervenciones más comunes fueron la sobredosificación (30,6%) y la subdosificación (18,8%). Se destacó la importancia del farmacéutico en la prevención de errores y en la mejora de la calidad de la farmacoterapia. La mayoría de los pacientes intervenidos fueron mujeres (61,2%). Además, se conoció que la metformina fue el medicamento más frecuentemente involucrado en las intervenciones farmacéuticas (45,9%). De tal manera se demostró la importancia del rol del farmacéutico en el Sistema de Distribución de Medicamentos en Dosis Unitarias y su contribución a la prevención de errores de medicación y la optimización de la farmacoterapia en estos pacientes. Además, se discuten las implicaciones de estos hallazgos en la práctica clínica y se proponen recomendaciones para futuras estrategias de gestión farmacéutica en esta población. Así mismo, estos resultados se examinan con el fin de evaluar la contribución de estas intervenciones a la seguridad y efectividad de los tratamientos farmacológicos. Se recomienda reforzar el seguimiento de las intervenciones farmacéuticas, continuar investigando su impacto a largo plazo, implementar programas de educación sobre adherencia al tratamiento y personalizar las intervenciones según las características individuales de cada paciente según los factores asociados a dicha enfermedad.
Keywords: DIABETES MELLITUS TIPO 2 (DM2); INTERVENCION FARMACEUTICA; DOSIS UNITARIA; ADHERENCIA